Perspectives on the 12 January 2020 Taal Volcano eruption: An analysis of residents’ narrative accounts - Martinez-Villegas, Ma. Mylene; Reniva, Paolo D.; Sanico, Lucille Rose D.; Loza, Allan R.; Seda, Ricardo G.; Doloiras, Dynie F.; Pidlaoan, Abigail C. (Frontiers in Earth Science, 2022)
This study reconstructs the 12 January 2020 Taal Volcano eruption through the analysis of narratives from two perspectives: those of the Taal Volcano Island (TVI) residents and those living along the Taal Caldera Lakeshore (TCLS). Personal accounts of TVI residents provide an up-close look at the volcano's behavior from the day before the eruption to the escalation of volcanic activity until the early morning after the eruption. These also include information on individual actions that led to community evacuation. The decisions and resulting actions of TVI residents highlight the importance of alertness to observations of changing volcano behavior (environmental cues) based on local knowledge and long-established communication between the monitoring agency and the residents that had trust in the received warning message during the unfolding event. These paved the way for the quick action of the residents to evacuate at the most critical time. Interviews of TCLS residents on the other hand show a spectator's first reaction to watching the bancas as TVI residents evacuate (social cues), before taking action to evacuate. While various information and education efforts were conducted years leading to the 2020 event, the lack of experiential knowledge among the lakeshore residents and considering that Taal did not have any major eruption in more than 40 years, mainly contributed to their hesitancy to immediately evacuate, not until the eruption occurred. Despite the occasional signs of unrest through the years, the long quiescence as perceived by the residents was a window to pursue various livelihoods- a major pull factor for the communities that thrived in the area. These sources of livelihood left behind during the evacuation remained the main motivator for the expressed desire of both the TVI and TCLS residents to return to the volcano island.